2011
DOI: 10.3109/00016489.2011.616911
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effectiveness of stellate ganglion block (SGB) treatment of sudden hearing loss

Abstract: Propensity score matching yielded 48 pairs. The mean therapeutic effect of the SGB was calculated to be 0.40 ± 0.20 (mean ± standard error, p = 0.051).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…The eventual involvement of internal ear circulatory disturbance causes metabolic disturbance of the inner ear cells, decreases in oxidation of metabolic substrates, and edema, resulting in irreversible changes. The resorption of edema is promoted by arterial relaxation from sympathetic blockade 6,15). Takinami15) reported that stellate ganglion block favorably affected outcomes in patients with unilateral SSNHL given a prior or concomitant course of systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eventual involvement of internal ear circulatory disturbance causes metabolic disturbance of the inner ear cells, decreases in oxidation of metabolic substrates, and edema, resulting in irreversible changes. The resorption of edema is promoted by arterial relaxation from sympathetic blockade 6,15). Takinami15) reported that stellate ganglion block favorably affected outcomes in patients with unilateral SSNHL given a prior or concomitant course of systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The resorption of edema is promoted by arterial relaxation from sympathetic blockade 6,15). Takinami15) reported that stellate ganglion block favorably affected outcomes in patients with unilateral SSNHL given a prior or concomitant course of systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effect was judged by comparing the mean hearing ability at presentation with that observed at the time that the patient's symptoms became nearly stable, based on the hearing improvement criteria described in the Report of the Survey Research Group of Acute Highly Impaired Hearing designated by the Ministry of Health and Welfare in 1985 (table 3). 5 Statistical analysis. A hierarchical cluster analysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…SGB is a well-established pain management procedure in wide use since 1920 with a high safety profile [30] and an extremely low complication rate of 1.7 per 1,000 procedures [31]. The procedure is commonly used to treat pain associated with many conditions including chronic regional pain syndrome (CRPS) types I and II, vascular insufficiency/occlusive vascular disorders of the upper extremities, postherpetic neuralgia, phantom limb pain or amputation stump pain, Quinine poisoning, sudden hearing loss and tinnitus, hyperhidrosis of the upper extremity, cardiac arrhythmias, ischemic cardiac pain, Bell's palsy, trigeminal neuralgia, migraine headaches, neuropathic pain, Meniere's syndrome and hot flashes [32][33][34][35][36][37][38][39][40].…”
Section: Sgb: Non-psychiatric Indications and Hypothesized Mechanism(mentioning
confidence: 99%